Computer Graphics: Theory and Practice - Gomes, Jonas; Velho, Luiz; Costa Sousa, Mario (A K Peters/CRC Press, 2012)
A complete and integrated introduction to computer graphics, this book focuses on conceptual aspects of computer graphics, covering fundamental mathematical theories and models and the inherent problems in implementing them. Only requiring basic knowledge of calculus and linear algebra, the text introduces the core challenges of the field and provides suggestions for further reading and studying on various topics. For each conceptual problem described, solution strategies are compared and presented in algorithmic form.